2009
DOI: 10.3354/dao02098
|View full text |Cite
|
Sign up to set email alerts
|

First detection of the amphibian chytrid fungus Batrachochytrium dendrobatidis in free-ranging populations of amphibians on mainland Asia: survey in South Korea

Abstract: Chytridiomycosis, a disease that has caused amphibian population declines globally and elevated many species of anurans to endangered or threatened status, has recently been declared an internationally notifiable disease. Batrachochytrium dendrobatidis (Bd), the amphibian chytrid fungus causing this disease, has not been previously reported in Korea or on mainland Asia. Thirty-six frog specimens representing 7 species were collected from the wild in South Korea and examined for Bd using standard PCR. Bd was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
3
34
0
2
Order By: Relevance
“…Aside from economic growth and development, emerging disease is another great cause threatening amphibian populations (Stauart et al, 2004). Recently, Yang et al (2009) revealed that chytridiomycosis, which can cause severe mortality rates in infected amphibians, was detected in wild populations in South Korea, indicating the need to pay more attention to amphibian conservation and protection. Despite the urgent need to understand these species better to efficiently protect and conserve them, very little information is available on the genus Hynobius thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from economic growth and development, emerging disease is another great cause threatening amphibian populations (Stauart et al, 2004). Recently, Yang et al (2009) revealed that chytridiomycosis, which can cause severe mortality rates in infected amphibians, was detected in wild populations in South Korea, indicating the need to pay more attention to amphibian conservation and protection. Despite the urgent need to understand these species better to efficiently protect and conserve them, very little information is available on the genus Hynobius thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of chytridiomycosis in the UK, for example, was associated with infected, feral, North American bullfrogs (Cunningham et al 2005). Invasive populations of the North American bullfrog have been documented across 4 continents, including Europe, North and South America, and Asia: of these, the majority of populations tested are positive for B. dendrobatidis (Hanselmann et al 2004, Garner et al 2006, Yang et al 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Bd infects at least 695 species of amphibians (anurans, salamanders, and caecilians) from all continents where they exist and has been implicated in the enigmatic disappearance of many frog species in Australia, Europe, and North, Central, and South America (Berger et al 1998, Lips et al 2006, Walker et al 2008, Vredenburg et al 2010, Cheng et al 2011, Soto-Azat et al 2013, Olson & Ronnenberg 2014. However, negative impacts at the population level on other regions where Bd exists, such as Asia and Africa, have not been recorded (Kusrini et al 2008, Goka et al 2009, Yang et al 2009, Bai et al 2010, Soto-Azat et al 2010, Savage et al 2011, Swei et al 2011. One possible explanation is that Bd is endemic in some areas but novel in others (Rosenblum et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, Bd has been described infecting wild and captive amphibians from many countries, including China, Japan, South Korea, Indonesia, Malaysia, Laos, Philippines, Sri Lanka, Kyrgyzstan, Vietnam, and India (Kusrini et al 2008, Une et al 2008, Goka et al 2009, Yang et al 2009, Bai et al 2010, Savage et al 2011, Swei et al 2011, Bataille et al 2013, Dahanukar et al 2013, Zhu et al 2014a). Nevertheless, extensive areas of central, northern, and western mainland Asia still lack information on the presence and impacts of Bd (Olson et al 2013, Olson & Ronnenberg 2014.…”
Section: Introductionmentioning
confidence: 99%